Pulmonary function assessment in patients with type 2 diabetes mellitus - Dr. Rekha Mehani; Dr. Sheema Maqsood (International Journal of Medical Research and Review, 2021)
Introduction: Diabetes mellitus is a leading public health problem all over the world. Diabetes mellitus is a risk factor that precipitating microvascular as well as macro-vascular pathologies. Several respiratory alterations have been reported in associations with Diabetes Mellitus. Therefore, the present study was designed to determine the effect of the disease on respiratory function in patients with diabetes.Method & material: For this study 54 Diabetes Mellitus patients were selected using simple random sampling from the diabetic clinic. 54 Non-diabetic, age & sex-matched subjects were also taken from teaching and non-teaching employees of the hospital for comparison.Result: In our study there was a statistically significant decrease in the level of FVC in DM patients compared to healthy male subjects. There was a statistically significant increase in the level of ratio of FEV1/FVC. A more sensitive index of early disease is FEV1/ FVC ratio.Conclusion: Spirometric values were consistently lower in subjects with diabetes mellitus than in non-diabetics. Subjects with poorer diabetic control have a worse spirometric function. We conclude that strict glycaemic control & regular breathing exercises to strengthen the respiratory muscles may improve the pulmonary function test in patients.